I think that I did this one correctly as well but I could not figure out the factoring. √x+2 + √3x+7=1 √3x+7 = 1-√x+2 √(3x+7)^2 =(1-√x+2)^2 3x+7=1-x = 2-2√x+2 3x+7 = -x+3-2√x+2 2x +4 = (-2√x+2) (2x+4)^2= (2√x+2)^2 4x^2+16x+16=4(x+2) 4x^2+12x-8=0
I think that I did this one correctly as well but I could not figure out the factoring. √x+2 + √3x+7=1 √3x+7 = 1-√x+2 √(3x+7)^2 =(1-√x+2)^2 3x+7=1-x = 2-2√x+2
...
Now plug in these solutions into the original equation and check which is a correct solution: